Polyhydroxybutyrate (PHB) production from crude glycerol by genetic engineering of Rhodotorula glutinis - Aristya, Ganies Riza; Lin, Yu-Ju; Chang, Jo-Shu; Chang, Jui-Jen; Yen, Hong-Wei (Elsevier Ltd., 2022)
Polyhydroxybutyrate (PHB) is a member of the Polyhydroxyalkanoates (PHAs) family, which is generally produced through microbial biosynthesis. The synthetic biology tools are applied to transform PHB genes (PhaA, PhaB and PhaC) into an oleaginous yeast (Rhodotorula glutinis) genome. Western blot analysis confirms the expression of PhaA, PhaB and PhaC in the candidate transformants. The strain of R. glutinis #100–29 was selected to be the best PHB production candidate according to the shaker results. As compared to glucose, crude glycerol was known to be a suitable carbon source for R. glutinis cultivation. The PHB concentration, yield and content obtained in a 5-L fermenter using 30 g/L of crude glycerol were 2.87 g/L, 95.53 mg/g and 62 respectively. To the best of our knowledge, these should be the highest numbers obtained in yeast for PHB production, which indicates that strain #100–29 could be a potential PHB producer from crude glycerol. © 2022 Elsevier Ltd